Fenugreek extract as an inducer of cellular death via autophagy in human T lymphoma Jurkat cells - Al-Daghri Nasser M; Alokail Majed S; Alkharfy Khalid M; Mohammed Abdul; Abd-Alrahman Sherif H; Yakout Sobhy M; Amer Osama E; Krishnaswamy Soundararajan (BMC, 2012)
Abstract Background Drugs used both in classical chemotherapy and the more recent targeted therapy do not have cancer cell specificity and, hence, cause severe systemic side effects. Tumors also develop resistance to such drugs due to heterogeneity of cell types and clonal selection. Several traditional dietary ingredients from plants, on the other hand, have been shown to act on multiple targets/pathways, and may overcome drug resistance. The dietary agents are safe and readily available. However, application of plant components for cancer treatment/prevention requires better understanding of anticancer functions and elucidation of their mechanisms of action. The current study focuses on the anticancer properties of fenugreek, a herb with proven anti-diabetic, antitumor and immune-stimulating functions. Method Jurkat cells were incubated with 30 to 1500 μg/mL concentrations of 50% ethanolic extract of dry fenugreek seeds and were followed for changes in viability (trypan blue assay), morphology (microscopic examination) and autophagic marker LC3 transcript level (RT-PCR). Results Incubation of Jurkat cells with fenugreek extract at concentrations ranging from 30 to 1500 μg/mL for up to 3 days resulted in cell death in a dose- and time-dependent manner. Jurkat cell death was preceded by the appearance of multiple large vacuoles, which coincided with transcriptional up-regulation of LC3. GC-MS analysis of fenugreek extract indicated the presence of several compounds with anticancer properties, including gingerol (4.82%), cedrene (2.91%), zingerone (16.5%), vanillin (1.52%) and eugenol (1.25%). Conclusions Distinct morphological changes involving appearance of large vacuoles, membrane disintegration and increased expression of LC3 transcripts indicated that fenugreek extract induced autophagy and autophagy-associated death of Jurkat cells. In addition to the already known apoptotic activation, induction of autophagy may be an additional mechanism underlying the anticancer properties of fenugreek. This is the first report showing fenugreek as an inducer of autophagy in human cells and further work is needed to define the various intermediates of the autophagic pathway.